Size-fractionated N2 fixation off the Changjiang Estuary during summer - Jiang, Zhibing; Zhu, Yuanli; Sun, Zhenhao; Zhai, Hongchang; Zhou, Feng; Yan, Xiaojun; Chen, Quanzhen; Chen, Jianfang; Zeng, Jiangning (Frontiers in Microbiology, 2023)
Recent evidence has shown active N2 fixation in coastal eutrophic waters, yet the rate and controlling factors remain poorly understood, particularly in large estuaries. The Changjiang Estuary (CE) and adjacent shelf are characterized by fresh, nitrogen-replete Changjiang Diluted Water (CDW) and saline, nitrogen-depletion intruded Kuroshio water (Taiwan Warm Current and nearshore Kuroshio Branch Current), where N2 fixation may be contributed by different groups (i.e., Trichodesmium and heterotrophic diazotrophs). Here, for the first time, we provide direct measurement of size-fractionated N2 fixation rates (NFRs) off the CE during summer 2014 using the 15N2 bubble tracer method. The results demonstrated considerable spatial variations (southern > northern; offshore > inshore) in surface and depth-integrated NFRs, averaging 0.83 nmol N L−1 d−1 and 24.3 μmol N m−2 d−1, respectively. The highest bulk NFR (99.9 μmol N m−2 d−1; mostly contributed by >10 μm fraction) occurred in the southeastern East China Sea, where suffered from strong intrusion of the Kuroshio water characterized by low N/P ratio (<10) and abundant Trichodesmium (up to 10.23 × 106 trichomes m−2). However, low NFR (mostly contributed by <10 μm fraction) was detected in the CE controlled by the CDW, where NOx concentration (up to 80 μmol L−1) and N/P ratio (>100) were high and Trichodesmium abundance was low. The >10 μm fraction accounted for 60% of depth-integrated bulk NFR over the CE and adjacent shelf. We speculated that the present NFR of >10 μm fraction was mostly supported by Trichodesmium. Spearman rank correlation indicated that the NFR was significantly positively correlated with Trichodesmium abundance, salinity, temperature and Secchi depth, but was negatively with turbidity, N/P ratio, NOx, and chlorophyll a concentration. Our study suggests that distribution and size structure of N2 fixation off the CE are largely regulated by water mass (intruded Kuroshio water and CDW) movement and associated diazotrophs (particularly Trichodesmium) and nutrient conditions.